Morphological features of rats' hearts after intrafetal injection of dexamethasone - Hryhorieva, O. A.; Chernyavskiy, A. V.; Guminskiy, Y. Y.; Григор'єва, Олена Анатоліївна; Чернявський, Артур Валерійович; Гумінський, Ю.Ю. (My University, 2021)
The aim: Is to study the morphological features of rats’ hearts after prenatal administration of glucocorticoids. Materials and methods: In this study we used histological, immunohistochemical, electron-microscopic and statistical research methods. Results: It is found that at 30th day after birth in rats after intrafetal introduction of dexamethasone in myocardium a relative area occupied by arterial vessels is significantly smaller in comparison with control. Absolute and relative number of Ki-67+-cardiomyocytes in the myocardium of experimental rats is reduced throughout the second week after birth and is significantly less compared to the control group. In the nuclei of cardiomyocytes of experimental rats is rendered the greater amount of heterochromatin in comparison with cardiomyocytes of the control group where euchromatin prevails. Conclusions: After intrafetal injection of dexametazone changes in dynamics and significantly smaller index of relative area occupied by arterial vessels in ventricular myocardium at the 30th day after birth are observed; the absolute and relative number of Ki-67+ -cardiomyocytes in myocardium decreases during the second week after birth and is significantly lower compared to the control group; in the nuclei of cardiomyocytes of experimental rats a greater amount of heterochromatin is visualized, and in cardiomyocytes of the control group – euchromatin.
Keywords: cardiomyocytes; heart; dexamethasone